Taraxacum officinale L. in leukemia and lymphoma: current knowledge and prospects for horticulture - Renna, Massimiliano (Frontiers in Plant Science, 2026)
Dandelion (Taraxacum officinale L.) is a globally distributed medicinal plant rich in phenolic acids, flavonoids, sesquiterpene lactones and pentacyclic triterpenoids. Preclinical studies indicate that dandelion extracts and isolated constituents exert selective cytotoxic and pro-apoptotic effects against various hematological malignancies, including leukemia and lymphoma, via mechanisms such as ROS generation, mitochondrial apoptosis, cell-cycle arrest and inhibition of oncogenic signaling (e.g., PI3K/AKT, STAT3). This mini-review synthesizes current in vitro and in vivo evidence on the antileukemic and antilymphoma potential of T. officinale, emphasizing the phytochemical classes most consistently implicated (notably triterpenoids like taraxasterol and pentacyclic acids) and highlighting methodological limitations of existing studies—dose relevance, lack of pharmacokinetic data and sparse safety profiling. Building on these pharmacological insights, horticultural strategies that can modulate bioactive profiles—controlled environment agriculture, hydroponics, elicitation, light spectral management and targeted nutrient fortification— are evaluated and a practical cultivation-to-clinic roadmap to produce standardized, high-value plant material suitable for translational research is proposed. Critical translational barriers, including standardization of extracts, potential interactions with anticancer drugs (notably tyrosine kinase inhibitors), and the need for rigorous toxicity and human pharmacology studies are also discussed. Finally, prioritized experimental and horticultural studies that would accelerate evidence-based development of dandelion-derived therapeutics for hematologic oncology are outlined, while cautioning against premature clinical use without controlled trials.